Media screening of lactic acid fermentation using Lactobacillus rhamnosus - Abdul Karim, Mohd Ismail; Mel, Maizirwan; Jamal, Parveen; Mohd salleh, Mohd Ramlan; Alamin, Noraini (Association of Agrilcutural Technology in SEA (AASEA), 2006)
rhamnosus) was successfully carried out in shake flask experiment. Initially eleven variables were screened using Placket Burman Design and the results indicated that, the main variables that affected the process were glucose and peptone. The correlation between those two variables was analyzed using Response Surface Methodology (RSM). The contour plot indicates that there is no significant interaction between these two variables.